EFFECT OF “GOLDEN PINEAPPLE INNOVATION” ON COSTA RICA'S PINEAPPLE EXPORTS TO U.S. MARKET: AN ECONOMETRIC APPROACH - Javier Paniagua-Molina; Luis Ricardo Solís-Rivera (International Journal of Food and Agricultural Economics, 2020)
An investigation was conducted on the effect of introducing a new variety of pineapple, known as golden pineapple (MD2) on the level of pineapple exports to the US market. Based on historical trade data from 1983 to 2017, a univariate structural econometric model was adjusted including variables related to export demand and isolating the effect of innovation through a binary control variable. The results obtained show that the effect of the innovation was a 25.27% increase in exports from Costa Rica to the North American market since the innovation was implemented. Conveniently, agricultural policymakers should consider similar studies to visualize the impact that innovation has on agricultural activities, and based on this, to plan, research, develop, and innovate programs within the agricultural sector.